2017
DOI: 10.3390/jcm6030031
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mitochondrial Respiratory Chain Activities in Muscle and Metabolites in Plasma and Urine: A Retrospective Study

Abstract: The relationship between 114 cases with decreased enzymatic activities of mitochondrial respiratory chain (MRC) complexes I-V (C I-V) in muscle and metabolites in urine and plasma was retrospectively examined. Less than 35% disclosed abnormal plasma amino acids and acylcarnitines, with elevated alanine and low free carnitine or elevated C4-OH-carnitine as the most common findings, respectively. Abnormal urine organic acids (OA) were detected in 82% of all cases. In CI and CII defects, lactic acid (LA) in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
7
0
3
Order By: Relevance
“…The result did not show any exonic variants in any of the known Fanconi anemia genes; however, there was a predicted homozygous disease-causing variant in the COX4I1 gene. As routine metabolic workup was normal (which does neither confirm nor exclude COX deficiency 22 ), functional studies were required and showed evidence of defective function of this gene confirming its role in the pathogenesis of the disease. Nevertheless, presently our findings do not fully explain the pathomechanistic link between a genetic, mitochondrial COX defect, and the Fanconi anemia-like presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The result did not show any exonic variants in any of the known Fanconi anemia genes; however, there was a predicted homozygous disease-causing variant in the COX4I1 gene. As routine metabolic workup was normal (which does neither confirm nor exclude COX deficiency 22 ), functional studies were required and showed evidence of defective function of this gene confirming its role in the pathogenesis of the disease. Nevertheless, presently our findings do not fully explain the pathomechanistic link between a genetic, mitochondrial COX defect, and the Fanconi anemia-like presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study by Alban and colleagues (2017), an abnormal organic acid profile was reported in 82% of the patients with a muscle MRC enzyme deficiency [25]. Patients with isolated MRC complex I and II deficiencies were found to have an elevated urine lactate level, and patients with isolated MRC complex IV and V deficiencies were found to have an increased urinary level of 3-methylglutaconic acid, which is an intermediate in mitochondrial metabolism of leucine, a branch chain amino acid [25]. Another common finding in the urine organic acid profile of these patients is the presence of elevated levels of dicarboxylic acids [6,26].…”
Section: Urine Organic Acidsmentioning
confidence: 99%
“…Numerous organic acids are present in the urine of patients who are reported to be clinically normal, although the actual concentration range for each of these acids can differ greatly, which may limit their diagnostic utility [24]. In a retrospective cohort study by Alban and colleagues (2017), an abnormal organic acid profile was reported in 82% of the patients with a muscle MRC enzyme deficiency [25]. Patients with isolated MRC complex I and II deficiencies were found to have an elevated urine lactate level, and patients with isolated MRC complex IV and V deficiencies were found to have an increased urinary level of 3-methylglutaconic acid, which is an intermediate in mitochondrial metabolism of leucine, a branch chain amino acid [25].…”
Section: Urine Organic Acidsmentioning
confidence: 99%
“…Urine organic acid analysis may reveal evidence of elevated lactate, Krebs cycle intermediates, or 3-methylglutaconic acid in some patients with MRC disorders; however, these metabolites may only be present if the patient is acutely symptomatic and be absent during periods of stability [ 2 ]. However, the diagnostic utility of urine organic acid analysis in mitochondrial disease is supported by the study of Alban et al (2017) [ 4 ], which reported an abnormal urine organic acid profile in 82% of patients with muscle MRC enzyme deficiencies. Nonetheless, renal immaturity is an important factor to consider, and an abnormal urine organic acid profile in a patient less than one year of age should be interpreted with extreme caution [ 2 ].…”
mentioning
confidence: 99%
“…A study by Morovat et al [ 8 ] has indicated that although serum FGF-21 determination may have diagnostic utility in mitochondrial disease, it may prove more useful in monitoring disease progression and the effects of therapeutic intervention. Furthermore, the combined use of serum FGF-21 determination with urine organic acid analysis has also been suggested to improve the diagnostic value of either test used in isolation [ 4 ]. Surprisingly, however, the combined assessment of both FGF-21 and GDF-15 in adult patients with mitochondrial disease was not found to improve the diagnostic value of the individual tests [ 7 ].…”
mentioning
confidence: 99%